Abandonment and management in Spanish dehesa systems: Effects on soil features and plant species richness and composition - Tárrega, Reyes; Calvo, Leonor; Taboada, Ángela; García-Tejero, Sergio; Marcos, Elena (Forest Ecology and Management, 2009)
Quercus pyrenaica dehesas have been traditionally used as communal extensive grazing systems in the Leo´n province (NW Spain). In this region, recent abandonment of rural areas and the subsequent gradual decrease in livestock load have led to the invasion of shrubs in the understory, increasing the risk of fires. Indeed, even if there is no need of creating new pasturelands for livestock breeding, the remaining landowners keep on burning to clear these montane patches. Alternatively, the regional administration encourages shrub cutting as a better way of managing these areas and preserving the pasturelands. Our aim was to determine the effects of the dehesa abandonment and shrub cutting on plant species richness (annual herbs, perennial herbs and woody plants) and species composition, as well as on topsoil properties. For that, we compared three types of dehesas with differentmanagement regimes: (1) grazed dehesas (used at the present), (2) abandoned dehesas (more than 20 years without grazing) and (3) dehesas where shrub cutting was applied after abandonment (i.e. cleared dehesas). We selected three replicates or stands per dehesa type. The highest organic matter content (O.M.), total nitrogen (N) and available phosphorus (P) were found in cleared dehesas, while the lowest values corresponded to the grazed ones. Abandoned dehesas were characterized by the highest values for available calcium (Ca2+). No significant differences were detected regarding the vegetation richness values (S alpha, gamma or beta), although higher mean values of S alpha and gamma were found in grazed dehesas, and lower values in the cleared ones. Concerning the vegetation life forms, grazed dehesas held significantly greater species richness and cover of annual herbs, while abandoned dehesas had significantly higher woody species cover. Both grazed and abandoned dehesas harboured plant species (38 and 13 species, respectively),which were exclusively found in one dehesa type. Contrary to that, cleared dehesas scarcely had ‘‘exclusive’’ species. To conclude, our results indicated that shrub cutting alone (not followed by livestock grazing) may cause loss of plant species richness, suggesting that it is not the most appropriate management method to restore vegetation, except for reducing the risk of fire.
Keywords: Land use change; management; Oak dehesa; Quercus pyrenaica; Species richness; Topsoil; Understory composition